Analysis of Difficulties of Science Teachers in Jayapura City in Conducting Class Action Research - Tanta; Ruth Megawati; Maik Akobiarek (Jurnal Penelitian Pendidikan IPA, 2023)
The teacher's understanding of student development determines the accuracy of the strategies used in teaching which of course has an impact on student learning outcomes. One of the things teachers can do to overcome problems in the classroom is to conduct Classroom Action Research (CAR). Researchers are interested in conducting research, namely knowing teachers' difficulties in implementing PTK and knowing the factors that influence teachers' difficulties in implementing PK. This research is quantitative and descriptive. The population in this study were all science teachers in the city of Jayapura, and the research sample was teachers who were active members of the MGMP Science in the city of Jayapura, totaling 60 people. The research instrument is a questionnaire which is examined in this case, namely the difficulties of teachers in implementing PTK and the factors that influence teachers' difficulties in implementing PTK. Data were analyzed descriptively. The research results obtained are as follows: teachers' difficulties in making PTK are divided into two, namely: Teachers' general understanding of PTK, namely: teachers have difficulty understanding the characteristics of PTK (purpose, procedures and making reports); Teachers' understanding, especially about PTK, is that teachers experience difficulties related to: The rules for writing PTK according to the standard rules for writing scientific papers; Make an analysis of the causes of PTK background; CAR Implementation Procedures (planning, implementation, observation and reflection); CAR methodology (subjects, instruments, analysis techniques, data processing); Conducting discussions (interpreting data for and while reflecting); Systematics of writing final reports. Furthermore, the factors that influence teachers' difficulties in making PTK are divided into 2: Internal factors and external factors.